Creating a Pharmacy Internship: A Toolbox for Success - Sarah Nisly; Lisa Brennan; Lauren Verbosky; Alexandre Raymond; Jennifer Tryon (University of Minnesota Libraries Publishing, 2018)
Objective: To describe available compensated student internships and provide guidance for new program development. Methods:  A search was conducted using PubMed, MEDLINE, and Google with the following search terms: pharmacy, intern, internship, and student.  All English language publications were considered for inclusion.  Articles describing IPPE or APPE student utilization were excluded. Key findings: Pharmacy student internship programs are common in practice, though there are few with published outcome data.  Most often, interns serve as pharmacist extenders and participate in activities that center around extension of pharmacy services within the institution.  Development of new programs should include partnering with nearby pharmacy programs and state boards of pharmacy to develop a well matched curriculum and allow for interns to practice at the top of their license.  Lastly, outcomes should be measured and disseminated for the benefit of the academy.  Additional considerations for developing a student internship program and guidance are provided. Conclusions: Although in existence for decades, minimal published reports showcase institutional outcomes associated with student internships.  No data is available to show the downstream effect an internship can have on direct patient care activities.   Article Type:  Note